National Sample Census of Agriculture 2007/2008 preliminary report - National Bureau of Statistics (Dar es Salaam Ministry of Finance, 2010)
The 2007/2008 Nationa Sample Census of Agriculture is the second census to be undertaken in the Poverty Monitoring System(PMS) of conducting censuses after every five years. The census aimed at providing the necessary information for policy formulation and development planning. It was also meant to provide data for monitoring Agricultural Sector Development (ASDP) and other agriculture and rural development programmes and facilitate specific interventions for most agricultural sector development programmes. This publication highlights the key findings of the census.
Includes the Swahili version of the report
Keywords: Census